Regional Mental Health Inequality in a Limited Data Region in the Northeast of Iran: A Decomposition Analysis - Vajihe Armanmehr; Zohreh Shahghasemi; Ali Alami; Sahar Babasafari; Shahab Rezaeian (Gonabad University of Medical Sciences, 2023)
Background: Limited information still exists about the distribution of mental health (MH) in small districts. Considering the diversity in cultural specifications of entities in different societies, the current study aimed-assess the inequality of poor MH and corresponding socio-demographic components in a general population. Methods: This population-based cross-sectional study was conducted in Gonabad City, North Eastern Iran. Data were collected by a general health questionnaire-28 (GHQ-28) assess MH status, considering a cut-off point of 23. The concentration index defines the inequality in the MH. Decomposition analysis was done-identify the contribution of each explanatory variable-the socioeconomic inequality in MH prevalence. Results: Eight hundred subjects were recruited (response rate=98%); approximately 41.6% were aged 30 years or younger, half of whom were females. The overall prevalence of poor MH was 24.7% (95% CI: 21.8-27.9%) and the age-adjusted prevalence of poor MH was 27.5% (95% CI: 24.2-31.2%). A concentration of poor MH prevalence was observed among the poorest people (concentration index: -0.15). Socioeconomic Status (SES) (59.7%), age (24.1%), and gender (4.7%) were identified as the main contributors-socioeconomic-related inequality in poor MH prevalence. Conclusion: Poor MH is significantly concentrated among the poorest people. Therefore, SES appeared-play a key role in improving the health of individuals, which can lead-improved health status in a community. Furthermore, these data suggest that the MH initiative should target the elderly and women via a recently determined family physician plan in Iran.